Hot-applied micro-aggregates for surface pavement layers - Loría Salazar, Luis Guillermo (2025)
One of the challenges associated with dense hot-mix asphalt is its tendency to suffer long-term permanent deformation, especially under harsh traffic loads and extreme weather conditions. Moreover, when such deformation occurs, it often leads to a gradual loss of surface texture, rendering the pavement smooth and potentially endangering road safety.